Performance of farmers in the future stock market in agricultural sector - Lima, Paulo (2013)
This study aimed to evaluate the performance of the Coopermibra associated members related to agricultural contracts future. The study was carried in the municipality of Campo Mourão, State of Paraná, Brazil, through a descriptive and qualitative method. The sample consisted of 40 cooperative members, who were interviewed in September/2008 during on-farm visits together technical assistants or during farmers ́ visits to the Cooperative. It was observed that 80% of the farmers perform early sales in the Cooperative branch. Among them, who can achieve a higher level of good decision (67.5%), are those that follow daily prices. The Cooperative works as an intermediary between the farmers and BM&F BOVESPA stock market because it has offered contracts to farmers for setting the price at the future at it branch, but it does not provide for the cooperative members a way to act directly in the market for derivatives. Such situation does not prevent the farmers to hold both types of contracts.